A Novel Reconfigurable Intelligent Surface-Supported Code Index Modulation-Based Receive Spatial Modulation System - Ozden, Burak Ahmet; Cogen, Fatih; Aydin, Erdogan; Ilhan, Haci; Basar, Ertugrul; Wen, Miaowen (IEEE, 2024)
Today's wireless communication networks have many requirements such as high data rate, high reliability, low latency, low error data transmission, and high energy efficiency. High-performance index modulation (IM) techniques and reconfigurable intelligent surface (RIS) technology, which has recently attracted the attention of researchers, are strong candidates to meet these requirements. This paper introduces a novel RIS-supported code IM-based receive spatial modulation (RIS-CIM-RSM) system. The proposed RIS-CIM-RSM system uses quadrature amplitude modulation (QAM) symbols, receive antenna indices, and spreading code indices for wireless data transmission. In the proposed system, an RIS applies a phase rotation that maximizes signal-to-noise ratio (SNR) to the signals coming to the reflecting elements and directs them to the selected receive antenna. Performance analyses of the proposed RIS-CIM-RSM system such as data rate, throughput, and energy saving are obtained. The results obtained show that the proposed RIS-CIM-RSM system is superior to the counterpart RIS-based IM systems in the literature in terms of data rate, throughput, energy saving, and error performance.
Keywords: Reconfigurable intelligent surface; index modulation; spatial modulation; code index modulation; quadrature amplitude modulation; bit error rate; wireless communications; Computer Science; Engineering; Telecommunications